Peran Amnesty International Pada Pembatasan Kebebasan Berekspresi Human Rights Defender di Indonesia: Studi Kasus Veronica Koman - M. Hafizh Nabiyyin; Stivani Ismawira Sinambela (Papua Journal of Diplomacy and International Relations, 2023)
This study aims to discover how Amnesty International plays a role as a Non-Governmental Organization in supporting the freedom of expression of Veronica Koman, a prominent human rights defender in Indonesia, and investigates its boomerang effect. This comparative analysis used a descriptive-qualitative method. The data collecting technique used literature study from official sources such as Amnesty International Indonesia’s website and Twitter, and other relevant sources, such as books, journals, and online news. This study finds that Amnesty International has played several roles such as: release responses on its website and social media; form a coalition and release a joint statement with other NGOs; launch PENA campaign; request Interpol to stop red notice on Veronica Koman; and advocacy to ICT Law and criminal code revision. By the end of 2021, Veronica Koman is still being hunted by the Indonesian government 2021. However, there is some visible progress in the terms of regulatory level.KEYWORDSAmnesty International; Freedom of Expression; Human Rights Defender; Indonesia; Veronica Koman